Opportunıty Recognısıtıon Among Sme Owner Managers/Entrepreneurs In Kampala, Uganda - Osunsan, Olutayo; Karuhanga, Robert (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Small and medium-sized enterprises (SMEs) are vital to economic growth and development in Uganda and contribute the attainment of several of the SDGs. However, high failure rates within the first five years of operation indicate a need to understand factors influencing SME success, particularly opportunity recognition by owner-managers. This study examines opportunity recognition among SME owner-managers in Kampala, Uganda, focusing on demographic factors such as age, gender, marital status, education level, and work experience. Data were collected from 193 respondents through closed-ended questionnaires, ensuring validity and reliability through the Content Validity Index (0.871) and Cronbach's Alpha (0.886). Analysis included independent t-tests, and One-Way ANOVA. Findings show no significant gender-based differences in opportunity recognition, suggesting the need for equitable support interventions. Age-related analysis indicates that opportunity recognition improves with age, with older entrepreneurs leveraging experience for incremental innovations. Marital status significantly influences opportunity recognition, with married owner-managers benefiting from supportive networks. Higher education levels, especially at the Master's level, correlate with enhanced opportunity recognition due to advanced cognitive skills and broader networks. Work experience length showed no significant impact, emphasizing the importance of quality experiences and targeted training. Recommendations include developing gender-equitable support, age-specific training programs, recognizing marital status impacts, encouraging higher education, and prioritizing quality work experiences over duration for effective opportunity recognition skill enhancement.